Behavioral Model of Middle-Aged and Seniors for Bicycle Tourism - Lin, Shu-Wang; Hsu, Shih-Yun; Ho, Juei-Ling; Lai, Mei-Ying (Frontiers in Psychology, 2020)
This research centers on the behavioral tendency of the middle-aged and seniors in bicycle tourism at environmentally protected scenic areas and its relevant influence factors. The theory of planned behavior (TPB) is adopted as the base of this study. The middle-aged and seniors are the subjects of this research. Questionnaire survey is conducted at environmentally protected national scenic areas in Taiwan. A total of 230 samples are drawn with the random sampling method and 210 are valid. The findings indicate two things. First, when applying TPB to different fields of study, the level of predictability may vary. Another finding is that subjective norm shows higher level of susceptibility to sport habit and predictability to behavioral intention than the other two constructs. With an empirical analysis, the study is able to provide middle-aged and senior participants and sport administration authorities with relevant suggestions for reference at the end of this paper.